The Role of Sufism as a Bridge-Builder to Foster Interfaith Dialogues and Communal Harmony (In Perspective of Subcontinent) - Prof. Dr. Matloob Ahmad,; Dr. Uzma Begum,; Kalsoom Akhtar (Corresponding Author),; Muhammad Arif Raza,; Mubashar Husnain, (Al-Qanṭara, 2023)
Sufism, often dubbed the mystical heart of Islam, found a distinctive and enriched expression when it permeated the subcontinent's socio-religious landscape. This essay undertakes a comprehensive examination of the evolution of Sufism in the region, tracing its journey from its initial inroads during the early invasions to its culmination as a syncretic force during the Mughal era and its interactions with modernity in the colonial period. By analyzing key historical events, influential Sufi figures, cultural adaptations, and the sociopolitical contexts that shaped its trajectory, we illuminate how Sufism, while maintaining its core tenets of spiritual introspection and Divine love, integrated local traditions and philosophies. This unique fusion, characterized by shared musical, artistic, and devotional practices, underscores Sufism's role as a bridge-builder in the subcontinent, fostering interfaith dialogues and communal harmony. In the face of challenges from puritanical movements to contemporary extremist ideologies, Sufism's enduring legacy in the subcontinent offers insights into the resilience and adaptability of spiritual traditions.